Development and Validation of Ferroptosis-Related LncRNA Biomarker in Bladder Carcinoma - Wang, Yiru; Zhang, Shijie; Bai, Yang; Li, Gen; Wang, Siyu; Chen, Jiayi; Liu, Xin; Yin, Hang (Frontiers in Cell and Developmental Biology, 2022)
Bladder cancer (BC) is a highly prevalent cancer form of the genitourinary system, however, the effective biomarkers are still ambiguous and deserve deeper investigation. Long non-coding RNA (lncRNA) occupies a prominent position in tumor biology and immunology, and ferroptosis-related genes participate in regulatory processes of cancer. In this study, 538 DE ferroptosis-related lncRNAs were identified from the TCGA database through co-expression method and differential expression analysis. Then the samples involved were equally and randomly divided into two cohorts for the construction of gene model and accuracy verification. Subsequently, a prediction model containing five ferroptosis-related lncRNAs was constructed by lasso and Cox regression analysis. Furthermore, in terms of predictive performance, consistent results were achieved in the training set, testing set and entire set. Kaplan-Meier curve, ROC area under the curve (AUC) and Principal Component Analysis (PCA) results verified the good predictive ability of model, and the gene model was confirmed as an independent prognostic indicator. In order to further investigate the mechanism, we explored the upstream of 5 lncRNAs and found that they may be modified by m6A to increase or decrease their expression in bladder cancer. Importantly, the low-risk group displayed higher mutation burden of tumors and lower TIDE score, which may be predicted to have a higher response rate to immunotherapy. While, interestingly the patients in high-risk group appeared to have a higher sensitivity to traditional chemotherapeutic agents through pRRophetic analysis. In general, our research established a 5-ferroptosis-related-lncRNA signature, which can be served as a promising prognostic biomarker for bladder cancer.